Etnos in demos - Türk, Danilo (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
ETHNOS AND DEMOS CELEBRATORY SPEECH AT THE 80TH ANNIVERSARY OF THE INSTITUTE FOR ETHNIC STUDIES. The article discusses the significance of the notions of ethnos and demos within the context of contemporary socio-political conditions and the role of the IES in these conditions in the 20th century. Historic experiences of the two notions are the basis of the IES scientific work. Its predecessor, the Minority Institute, established in the political circumstances of the Versailles international regulation of Europe after the WW I, contributed significantly to the discussion of minority protection of that period. After the WW II. the element of demos prevailed in Europe, while ethnos was marginalized. Nevertheless, minority issues were treated differently. At the end of the Cold war, with new political conditions, ethnic issues regained importance. In all this time and especially since the 1960s, the IES had an important role in the development of scientific methods and solutions in the field of political and international legal regulation of minority issues, above all those concerning the Slovenes in Austria and Italy.The article lists contemporary topics, researched at the IES. Apart from the traditional ones, these are also the status of immigrants in Slovenia,constitutional and legal issues, such as the principle of non-discrimination, Roma issues, regulation and solving of conflicts. A far-fetching challenge for the IES may be its role in the future understanmding of ethnic phenomena in contemporary social conditions and solving of the thereof arising issues.
Keywords: raziskovalni inštituti; Inštitut za narodnostna vprašanja (Ljubljana); zgodovinski pregledi